Factors Affecting the Oral Healthcare-seeking behavior of call center agents in Arriva Medical Philippines - Buchan, Patricia Pamela G.; Cruz, Patricia Grace G.; Arevalo, Jean C.; Estrera, Kristine Rachelle P. (Manila Department of Community Dentistry, University of the Philippines Manila, 2017)
INTRODUCTION: Healthcare-seeking behavior is the decision to engage in the utilization of healthcare systems. Factors such as socio-economic variables, demographics, type of illness, access to services, and perceived quality of services influence this behavior (MacKian,2003). Call center agents are those who handle incoming/outgoing calls for a business, account inquiries, and customer complaints. Their environment poses concerns in their health including oral health.
METHODS: 114 call center agents of Arriva Medical Philippines participated in answering a 9-item questionnaire about the factors affecting their oral healthcare-seeking behavior. Results were tabulated using Microsoft Excel.
RESULTS: It was found that the call center agents in Arriva Medical Philippines visit the dentist every 6 months, when there is pain or discomfort, and for oral prophylaxis. HMO/company dentist is preferred over private/family dentist. Their dentist preference is attributed to convenient location. Perceived quality of service for both types of dentist affects their decision to seek dental service from the same dentist. Their problem in getting dental care was conflict with scheduling. Past experiences of those close to them do not affect their oral healthcare-seeking behavior. They use toothbrush and toothpaste more often than the recommended frequency by ADA. Furthermore, they use dental aids such as dental floss, mouth rinse, and tongue cleaner.
CONCLUSION: The researchers have deduced that access to services, perceived quality of service, time conflict, and pain or discomfort affect the oral healthcare-seeking behavior of call center agents in Arriva Medical Philippines.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Oral health; Call center agents--Philippines.; Arriva Medical--Philippines.